Dome-Shaped Pituitary Enlargement in Primary Hypothyroidism: Avoiding Neurosurgical Interventions - Chakraborty, Satyam; Tiwari, Mona; Palui , Rajan; Bhattacharya, Kajari; Gangopadhyay, Kalyan Kumar (Journal of the ASEAN Federation of Endocrine Societies, 2020)
We describe three cases of primary hypothyroidism which presented initially to neurosurgery department with pituitary hyperplasia. We have found a novel pattern of ‘dome-shaped’ enlargement of pituitary in MRI of these patients. Out of these 3 patients, in two of them, the planned surgery was deferred when endocrinologists were consulted and the pituitary hyperplasia completely resolved with levothyroxine treatment. In the third case, pituitary surgery was already performed before endocrinology consultation and histopathology revealed thyrotroph hyperplasia. The hyperplastic lesions described typically have a homogenous symmetrical ‘dome’ shaped architecture unlike the non-functioning pituitary adenoma (NFPA), which usually might often be of varying shapes and homogeneity. Analysis of pituitary images from similar case reports published in literature, also showed this typical ‘dome’ shaped pituitary enlargement. This imaging characteristic can be a clue to look for underlying hormone deficiency, especially in primary hypothyroidism. Therefore, a thorough endocrine evaluation especially looking for primary hypothyroidism in such dome-shaped pituitary lesions is mandatory to prevent unwarranted neuro-surgical intervention as treatment of primary hypothyroidism may result in resolution of the abnormal enlargement.